Customer-oriented approach as basis of increase of efficiency of administrative activity - T. V. Saprykina (Путеводитель предпринимателя)
The economy of Russia undergoes complex changes now and economic entities need to adapt for the developed business conditions as soon as possible. In article need of implementation of customer-oriented approaches to business is opened, the concepts «efficiency» and «productivity» of economic object are specified. The concepts «loyalty» and «satisfaction» of consumers and their influence on efficiency of administrative activity are considered.